Empowerment of Village Owned Enterprises (BUMDes) in the Context of Optimizing the Assets of Nyuhtebel Village, Manggis District, Karangasem Regency - Marhaeni, A.A.I.N; Nyoman Yuliarmi, Ni; Nyoman Reni Suasih, Ni; Jati Primajana, Dewa; W Priyana Agus Sudharma, I; Sinthya Aryasthini M, Made; Made Putra Yasa, I (CV. Inara, 2022)
Optimizing the assets owned by the village is very important in order to increase the welfare of the village community in a sustainable manner. Village-owned Enterprises (BUMDes) are village-owned business entities that have a very strategic role as a pillar of village hopes to improve the welfare of its people. In order for Bumdes to develop more quickly, Bumdes really need to be empowered according to their respective potentials. The purpose of this activity in general is to identify village potential that can be developed, find suitable business activities to implement, identify community needs that can be handled by BUMDes, encourage village community participation in BUMDes development. The methods used include observing village conditions, providing outreach to village communities, conducting interviews, and analyzing data obtained from these activities. The results of this activity are 1) Finding some tourism potential in Nyuhtebel Village. Such as jogging track, village library, Bukit Batu Gede, and BUMdes Café and Batu Madeg Beach; 2) Provide recommendations to Nyuhtebel Village officials regarding business activities that are suitable for implementation in the Village and in accordance with community needs, such as creating a business line as a supplier, this is in line with the environment of Nyuhtebel Village which coincides with the tourism sector. Thus, it is easier for tourism actors in the area to access purchases of supporting tourism needs such as vegetables, mineral water, kitchen equipment, toiletries, etc.; 3) recommend potential that is in accordance with the current conditions of the Village and the needs of the community so that BUMDes are expected to be able to improve community welfare. The potential for Nyuhtebel Village that is suitable for viewing the environment of Nyuhtebel Village as a tourism buffer zone is to create a business line related to tourism such as supplying hotel & restaurant needs; 4) Providing understanding to the community to actively participate in BUMDes and educating the community about the importance of BUMDes as a locomotive for accelerating village economic growth. Suggestions and requests from village officials, so that Community Service activities can evaluate both previous activities or strategic plans that have been designed by Nyuhtebel Village.